Chemical characteristics analyze of SBS-modified bitumen containing composite nanomaterials after aging by FTIR and GPC. (21st March 2022) - Zhang, Dongmei; Zheng, Yuanming; Yuan, Guangchen; Qian, Guoping; Zhang, Henglong; You, Zhanping; Li, Ping
Highlights: The aging rate of EVTS and OMTS was less than that of SBS-modified bitumen. OEVMT/TiO2 and OMMT/TiO2 reduced the growth rate of LMS during aging. Composite nanomaterials reduced the influence of UV light on bitumen aging. Composite nanomaterials reduced the oxidation degree of bitumen. Abstract: To improve the thermal-oxidation aging resistance and anti-ultraviolet (UV) aging of SBS-modified bitumen. Nanometer-titania (nano-TiO2 ) was compounded with organically expanded vermiculite (OEVMT) and organic montmorillonite (OMMT) to prepare composite nanomaterials (OEVMT/TiO2 and OMMT/TiO2 ). The results showed that OEVMT/TiO2 and OMMT/TiO2 improved the anti-deformation ability of SBS-modified bitumen. Under the same aging conditions, the carbonyl index ( CI ) and butadiene index ( BI ) of the composite nanomaterials modified bitumen had smaller changes than the original bitumen. At the same time, it was found that OEVMT/TiO2 and OMMT/TiO2 significantly reduced the LMS growth rate of original bitumen, which effectively inhibited the transfer rate of small and medium molecular size to LMS during the aging process.